2013
DOI: 10.1136/ejhpharm-2013-000276.179
|View full text |Cite
|
Sign up to set email alerts
|

GRP-179 Switch from CERA to EPO Zeta in Patients with Anaemia and Chronic Kidney Disease

Abstract: Background As the result of a possible shortage of methoxy polyethylene glycol epoetin beta (CERA) within Italy, with the agreement of the EMA, AIFA (the Italian Medicines Agency) prepared a document inviting prescribers to switch patients who were undergoing treatment with different doses of CERA to any Erythropoiesis Stimulating Agent (ESA), for the treatment of anaemia associated with chronic kidney disease (CKD). This recommendation emphasised the need to monitor haemoglobin levels (Hb) and safety and effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, ESAs are very expensive and access to them is likely to be restricted. With the advent of biosimilars, drug access and treatment options improved adding potential health economic benefits over the reference biopharmaceutical ESA therapy 87,88,93,94,96. In one survey in Spain, the epoetin zeta cost analysis reported a total cost saving of nearly 45% with respect to epoetin alfa 97.…”
Section: Pharmacoeconomic Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, ESAs are very expensive and access to them is likely to be restricted. With the advent of biosimilars, drug access and treatment options improved adding potential health economic benefits over the reference biopharmaceutical ESA therapy 87,88,93,94,96. In one survey in Spain, the epoetin zeta cost analysis reported a total cost saving of nearly 45% with respect to epoetin alfa 97.…”
Section: Pharmacoeconomic Considerationsmentioning
confidence: 99%
“…Eight studies reported the safety of epoetin zeta in patients with renal anemia. Of those, there are four clinical trials, 24 , 28 , 41 , 79 three observational studies, 76 , 81 , 87 and one post hoc analysis based on two clinical trials. 88 Table 4 summarizes the common adverse events observed in more than 5% of the patients in the four clinical trials.…”
Section: Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies reported the safety of epoetin zeta in patients with renal anemia. Of those, there are four clinical trials, 9,10,16,18 three observational studies, 14,30,31 and one post-hoc analysis based on two clinical trials. 26 Again there was no reported cases of anti-epoetin antibodies or PRCA associated with the administration of epoetin zeta in these trials.…”
Section: Discussionmentioning
confidence: 99%